Photoreflectance and Raman Study of Surface Electric States on AlGaAs/GaAs Heterostructures - Luis Zamora-Peredo; Leandro García-González; Julián Hernández-Torres; Irving E. Cortes-Mestizo; Víctor H. Méndez-García; Máximo López-López (Journal of Spectroscopy)
Photoreflectance (PR) and Raman are two very useful spectroscopy techniques that usually are used to know the surface electronic states in GaAs-based semiconductor devices. However, although they are exceptional tools there are few reports where both techniques were used in these kinds of devices. In this work, the surface electronic states on AlGaAs/GaAs heterostructures were studied in order to identify the effect of factors like laser penetration depth, cap layer thickness, and surface passivation over PR and Raman spectra. PR measurements were performed alternately with two lasers (532 nm and 375 nm wavelength) as the modulation sources in order to identify internal and surface features. The surface electric field calculated by PR analysis decreased whereas the GaAs cap layer thickness increased, in good agreement with a similar behavior observed in Raman measurements (IL-/ILO ratio). When the heterostructures were treated by Si-flux, these techniques showed contrary behaviors. PR analysis revealed a diminution in the surface electric field due to a passivation process whereas the IL-/ILO ratio did not present the same behavior because it was dominated by the depletion layers width (cap layer thickness) and the laser penetration depth.